Which Doctor? Combining Vignettes and Item Response to Measure Doctor Quality - Das, Jishnu (World Bank, Washington, D.C., 2013)
The authors develop a method in which vignettes-a battery of questions for hypothetical cases-are evaluated with item response theory to create a metric for doctor quality. The method allows a simultaneous estimation of quality and validation of the test instrument that can be used for further refinements. The authors apply the method to a sample of medical practitioners in Delhi, India. The method gives plausible results, rationalizes different perceptions of quality in the public and private sectors, and pinpoints several serious problems with health care delivery in urban India. The findings confirm, for instance, that the quality of private providers located in poorer areas of the city is significantly lower than those in richer neighborhoods. Surprisingly, similar results hold for providers in the public sector, with important implications for inequities in the availability of health care.